Perception of undergraduates on study habit strategies for overcoming examination anxiety in Kwara, Nigeria - Agubosi Lydia Akunna; Falilat Anike Okesina; Samuel Kolawole Ajiboye; Omotayo Esther Monisola (Humanitas: Indonesian Psychological Journal, 2022)
Examination anxiety has made students fail their examinations, causing many problems, including depression and suicide. The study aimed to investigate study habit strategies for overcoming examination anxiety as perceived by undergraduate students in Kwara State, Nigeria. The influence of gender, academic level, and age on strategies for handling examination anxiety were also investigated. A descriptive survey was adopted, with a sample of 250 respondents selected through a multistage sampling procedure to participate. Data was collected through Study Habit for overcoming Examination Anxiety Questionnaire (SHEAQ). The instrument was validated by four experts in measurement and has a good reliability coefficient obtained through test re-test. One research question and three hypotheses guided the study. Based on data analysis with t-test and ANOVA, hypothesis 1 was retained, while hypotheses 2 and 3 were rejected. Findings showed that overcoming examination anxiety as perceived by respondents are: reviewing what was taught, having adequate time for study, and testing oneself, among other strategies. Findings also showed no significant difference in the strategies for overcoming examination anxiety based on gender; significant differences were found based on academic level and age. Therefore, students should be counseled on the need to develop good study habits to pass examinations.